2013
DOI: 10.1162/rest_a_00371
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Use of Labor Market Policies: The Role of Job Search Assistance

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
(64 reference statements)
0
23
0
2
Order By: Relevance
“…At the same time, caseworkers may also target discouraged workers with very low employment probabilities just to prequalify them for the receipt of unemployment benefits (churning effect) 163 . Nonetheless, evidence by Wunsch (2013) underlines that job search assistance should be targeted at unemployed workers with low hiring probabilities, since these are the ones needing assistance in avoiding becoming long-term unemployed 164 , and beyond that at long-term unemployed workers. Card et al (2010), Kastoryano and van der Klaauw (2011) and Wunsch (2013) confirm previous results that ALMPs improving job matching should be applied at the beginning of the unemployment spell.…”
Section: Improved Labor Market Matching (Category V)mentioning
confidence: 99%
“…At the same time, caseworkers may also target discouraged workers with very low employment probabilities just to prequalify them for the receipt of unemployment benefits (churning effect) 163 . Nonetheless, evidence by Wunsch (2013) underlines that job search assistance should be targeted at unemployed workers with low hiring probabilities, since these are the ones needing assistance in avoiding becoming long-term unemployed 164 , and beyond that at long-term unemployed workers. Card et al (2010), Kastoryano and van der Klaauw (2011) and Wunsch (2013) confirm previous results that ALMPs improving job matching should be applied at the beginning of the unemployment spell.…”
Section: Improved Labor Market Matching (Category V)mentioning
confidence: 99%
“…In the following, we will use the terms "establishment" and "firm" interchangeably. 12 The social insurance records were also used, for example, by Wunsch and lechner (2008), lechner and Wunsch (2013), Wunsch (2013), and biewen, fitzenberger, Osikominu, and Paul (2014) but with a different sampling design. as to whether the firm offers PWe.…”
Section: Definition and Measurement Of The Treatmentmentioning
confidence: 99%
“…21 see, for instance, Mackinnon (2006) for a discussion of bootstrapping symmetric statistics. since the theoretical results by Abadie and Imbens (2006) and the simulation-based results in huber, lechner, and Wunsch (2013) suggested that the estimator is asymptotically normally distributed, bootstrapping the potentially pivotal t-statistic (computed under the assumption that the weights obtained to compute the control group are non-stochastic) has the advantage of potentially providing so-called asymptotic refinements and thus improving inference. We also checked the bootstrap distribution of the estimated effects directly (quantile method).…”
Section: Descriptive Statistics and Balancing Testsmentioning
confidence: 99%
“…They comprise employment, unemployment and earnings histories, as well as a rich set of personal characteristics for all workers employed by the firms in our data on June 30, 2002. The social insurance records have also been used, for example, by Wunsch and Lechner (2008), Biewen et al (2013), Wunsch (2013), and Lechner and Wunsch (2013), with a different sampling design, though. Finally, the data also contain a rich set of regional characteristics, merged via county identifiers from regional statistics, such as the federal state, urbanization, and local labour market conditions.…”
Section: Firms' Health Policies In Germanymentioning
confidence: 99%